Comparative policing from a legal perspective - Boer, Monica den (Research handbooks in comparative law, 2018)
Public police forces are a regular phenomenon in most jurisdictions around the world, yet their highly divergent legal context draws surprisingly little attention. Bringing together a wide range of police experts from all around the world, this book provides an overview of traditional and emerging fields of public policing. In this Research Handbook, academics and practitioners explore the relationship between policing and the law and focus on case material and human rights issues. The book concludes that public policing is far from self-evident, particularly in an era where more emphasis is placed upon private security, anti-terrorism and modern technology. As digital and global societies demand new solutions to rapidly changing social challenges, public police will undergo a transformation. New material and findings are presented with an international-comparative perspective. It is a must-read for students of policing, security and law and professionals in related fields.